SUBSTITUSI DAGING DENGAN HATI IKAN PATIN (Pangasius hypophthalmus) PADA BAKSO IKAN SEBAGAI MAKANAN SELINGAN SUMBER Fe BAGI REMAJA - Olivia Melisa; Widawati; Eka Roshifita Rizqi (Jurnal Spektrum Kesehatan Indonesia, 2026)
Subtitution of fish meatballs from striped catfish with its liver are a processed food product that utilizes striped catfish liver as a source of iron (Fe). Commercially available meatballs are generally not formulated as iron-rich foods, whereas adolescents are a group vulnerable to anemia and require adequate iron intake to support growth and daily activities. This study aimed to determine the best formulation of striped catfish liver meatballs, analyze their nutritional content, and evaluate their feasibility as an iron-rich food. The research was carried out in 2025 using a Completely Randomized Design (CRD) with one control and three treatment formulations, namely F0 (100% striped catfish meat), F1 (90% striped catfish meat + 10% striped catfish liver), F2 (80% striped catfish meat + 20% striped catfish liver), and F3 (70% striped catfish meat + 30% striped catfish liver). Proximate analysis and iron content analysis were conducted in the laboratory, while organoleptic evaluation was carried out descriptively with 25 panelists. The results of the organoleptic test showed that formulation F1 was the best formulation, with an acceptance rate of 95%. The nutritional composition of F1 meatballs per 100 grams consisted of 45.22% moisture, 0.90% ash, 19.51% protein, 5.20% fat, 29.02% carbohydrates, 0.35% calcium, and 19.5 mg of iron. The iron content was categorized as high and met the criteria for an iron-rich food according to BPOM regulations (2022). In addition to having good nutritional quality and acceptability, F1 meatballs were also more economical than the control. This study recommends further development of striped catfish–based processed food products to enhance local food diversification and add value to the fisheries industry, as well as further research on other micronutrients such as vitamin A, phosphorus, and zinc (Zn), and formulation innovations through the addition of spices or natural ingredients to improve flavor, aroma, and product competitiveness.